2019
DOI: 10.15587/2519-4852.2019.182412
|View full text |Cite
|
Sign up to set email alerts
|

Studies of physico-chemical and pharmaco-technological parameters of bioflavonoids diosmin and hesperidin

Abstract: Незважаючи на підвищений попит на синтетичні лікарські засоби, використання субстанцій рослинного походження є перспективним напрямком розвитку фармацевтичного сектору галузі охорони здоров'я України. Субстанціями рослинного походження, що мають широкий спектр дії та можуть використовуватися для лікування захворювань судин, в тому числі і терапії захворювань аноректальної зони-є діосмін та гесперидин. На фармацевтичному ринку України дані субстанції представлені виключно твердими лікарськими формами, що застос… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Thus, according to the results of previous studies, we have selected phleboprotective substances diosmin and hesperidin as API [9]. During the Ukrainian pharmaceutical market research, it was found that this combination of active substances is used only in oral dosage forms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to the results of previous studies, we have selected phleboprotective substances diosmin and hesperidin as API [9]. During the Ukrainian pharmaceutical market research, it was found that this combination of active substances is used only in oral dosage forms [10].…”
Section: Introductionmentioning
confidence: 99%